Heterogeneous Fenton Degradation Of Ofloxacin In Aqueous Solution Using Fe3O4-Zeolite, Fe3O4-Montmorillonite And Fe3O4-Montmorillonite Alginate Composites - Dhahawi, Alamri Rahmah (2023)
The primary aim of this study is to develop an economical, stable and effective heterogeneous catalyst for wastewater remediation via the Fenton oxidation process. Fe3O4 can effectively activate H2O2 to produce hydroxyl radicals, but the particles agglomerate easily. To solve this problem, Fe3O4-zeolite (FeZ) and Fe3O4-montmorillonlite (FeM) composites were synthesized via a facile co-precipitation method and characterized using various techniques. The performance of each of the catalysts was evaluated via the Fenton degradation of ofloxacin (OFL), an antibiotic and a recalcitrant pollutant because of its high activity and poor biodegradability. The effect of parameters such as amount of Fe precursor, catalyst dosage, initial solution pH, initial OFL concentration, different oxidants, H2O2 dosage, reaction temperature and inorganic salts on the OFL removal percentage were investigated. Loading of Fe3O4 onto zeolites resulted in the formation composites with higher surface area and pore volume. Experimental results revealed that as much as 88% OFL from the aqueous OFL solution 20 mg/L and 51.2% total organic carbon (TOC) could be removed in 120 min using FeZ-8 catalyst at the optimum condition. Since montmorillonite is capable to adsorb OFL at higher concentration, the OFL initial concentration was adjusted to 50 mg/L for FeM.